Relationship of Interpersonal Management Communications with the Work Participation of Karang Taruna Members in Sungai Sirah, Padang Pariaman Regency - Roni Kamal; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by the low work participation of members of Youth Organization, the authors' allegation is caused by the lack of interpersonal communication carried out by the manager of Tunas Cemerlang Karang Taruna in Nagari Sungai Sirah, Sungai Geringging, Padang Pariaman District. This study aims to: 1) describe the interpersonal communication of the Youth Organization manager; 2) describe the work participation of Karang Taruna members; and 3) see the interpersonal communication relationship between managers and the participation of Karang Taruna members in Sungai Sirah, Sungai Geringging District, Padang Pariaman Regency. This research is a correlational quantitative study. The population is all 120 members of Karang Taruna Tunas Cemerlang. While the sample was taken as much as 50% of the population of 60 people with a stratified random sampling technique. Data collection techniques using a questionnaire while the data collection tool using data questionnaires obtained were analyzed using descriptive analysis and correlational (product-moment). The results of this study indicate: 1) interpersonal communication management of Karang Taruna Tunas Cemerlang is still low; 2) the work participation of members of Karang Taruna Tunas Cemerlang is very low; and 3) there is a significant relationship between manager's interpersonal communication with the work participation of Karang Taruna members in Sungai Sirah Geringging, Padang Pariaman Regency.Keywords: Interpersonal Communication, Work Participation, Youth Organization